Review of electrochemical oxidation desulfurization for fuels and minerals. (1st December 2021) - Zhang, Tong; Zhang, Jintao; Wang, Zhi; Liu, Junhao; Qian, Guoyu; Wang, Dong; Gong, Xuzhong
Highlights: Five key steps were proposed during electro-desulfurization; The progress on promotion of key steps was summarized; The synergistically design of cell, electrolyte and electrode was claimed; Bottleneck of electro-oxidation desulfurization with different states was analyzed; Strengthening methods of three transfer and two reactions were emphasized. Abstract: Electro-oxidation desulfurization uses reactive oxygen species (ROSs) from water electrolysis to strengthen the transition of sulfur-containing phase, enhancing the separation property between sulfur and fuel. In this process, the rate-determine step is considered as the precise contact between ROSs and sulfur. "Three transfers and two reactions" play critical roles in improving the contact, which are 1) the ROS precursor transfer, 2) transfer of ROSs, 3) transfer of sulfur, 4) the formation of ROSs, 5) the oxidation reaction between sulfur and ROSs. The synergy "three transfers and two reactions" can be improved by regulating the electrode structure and corresponding external field. Therefore, the enhancement of "three transfers and two reactions" can be designed from three aspects: 1) the design of electrolysis cell, 2) the regulation of electrolyte system, and 3) the design of electrode structures. In this review, we briefly introduced the mechanism of electro-oxidation desulfurization, and proposed key steps during electro-desulfurization and summarized development of approaches to enhance those key steps with emphasis on the bottlenecks in different sulfur phases. We also reviewed recent attractive progresses in the design of electrolyte and cells for improving the reactant solubility, which is very critical for heterogeneous reactions to realize large-scale industrial applications.